2007
DOI: 10.1016/j.apcatb.2007.02.019
|View full text |Cite
|
Sign up to set email alerts
|

Improved performance of non-thermal plasma reactor during decomposition of trichloroethylene: Optimization of the reactor geometry and introduction of catalytic electrode

Abstract: The decomposition of trichloroethylene (TCE) by non-thermal plasma was investigated in a dielectric barrier discharge (DBD) reactor with a copper rod inner electrode and compared with a plasma-catalytic reactor. The particularity of the plasma-catalytic reactor is the inner electrode made of sintered metal fibers (SMF) coated by transition metal oxides. In order to optimize the geometry of the plasma reactor, the efficiency of TCE removal was compared for different discharge gap lengths in the range of 1-5 mm.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
58
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 120 publications
(60 citation statements)
references
References 28 publications
2
58
0
Order By: Relevance
“…The by-product analysis indicates that TCE is only partially mineralized. This demonstrates one of the shortcomings of NTP which can be improved by catalyst hybridization [14][15][16]. Figure 3 shows the effect of the initial TCE concentration on the RE for both negative and positive corona.…”
Section: Identification Of By-productsmentioning
confidence: 98%
“…The by-product analysis indicates that TCE is only partially mineralized. This demonstrates one of the shortcomings of NTP which can be improved by catalyst hybridization [14][15][16]. Figure 3 shows the effect of the initial TCE concentration on the RE for both negative and positive corona.…”
Section: Identification Of By-productsmentioning
confidence: 98%
“…Control of VOCs in the atmosphere is a major environmental problem now and attracts more and more researchers' attentions (Futamura et al, 1997;Muhamad et al, 2000;Gal et al, 2003;Magureanu et al, 2005;Malik et al, 2005;Kim, 2006;Magureanu et al, 2007;Juang et al, 2009a;Zhu et al, 2009a). As one of the typical VOCs, toluene effluents came from many industries, including paints, paint thinners, fingernail polish, lacquers, adhesives, rubber and some print and leather tanning processes.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, non-thermal plasma has attracted much attention as an method for VOCs control for two decades due to its unique properties such as quick response at ambient temperature, achievement of high electron energies within short residence times, system compactness, and easy operations (Muhamad, 2000;Li et al, 2006). In order to improve the energy efficiency of the VOCs decomposition process by the plasma, the cooperation with catalyst has been tested by some researchers (Einaga et al, 2001;Guo et al, 2006;Jim, 2008;Krawczyk, 2001;Magureanu et al, 2007a and b;Ogata et al, 2003;Wallis et al, 2007;Li et al, 2007;Zhu et al, 2007b). These studies showed that the combination of discharge plasma with catalyst is a very effective method in VOCs removal.…”
Section: Introductionmentioning
confidence: 99%